Global warming will reduce female production in Aphytis melinus: Implications for the biological control of Aonidiella aurantii and its coexistence with A. chrysomphali - Cebolla, Ruth; Urbaneja, Alberto; Tena, Alejandro (2018)
In recent years, it has been emphasized that global warming could disrupt the efficacy and prevalence of some biocontrol agents. An increase of about 3ºC is predicted by the end of the twenty-first century in the Mediterranean basin (IPCC, 2014). In this context, we investigated the influence of the predicted temperature in the efficacy and competition of two sympatric parasitoids of the genus Aphytis (Hymenoptera: Aphelinidae), which regulate the populations of the California red scale Aonidiella aurantii (Hemiptera: Diaspididae) in Mediterranean citrus. The potential of A. chrysomphali as biological control agent of A. aurantii was reduced when both parasitoids compete within the same patch at the current and expected temperatures. These results support that A. melinus is a superior competitor and can displace the native A. chrysomphali, unless it is able to avoid interspecific competition by using hosts of smaller size. Interestingly, the increase of temperature caused a higher production of males in A. melinus, which could destabilize the current balance between this parasitoid and its host in favour towards the host. This study highlights the importance of understanding how global warming affects species interactions and how these changes will probably impact current successful biological control programs.